2012
DOI: 10.4161/epi.21915
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient status and global DNA methylation in school-age children

Abstract: Aberrations in global LINE-1 DNA methylation have been related to risk of cancer and cardiovascular disease. Micronutrients including methyl-donors and retinoids are involved in DNA methylation pathways. We investigated associations of micronutrient status and LINE-1 methylation in a cross-sectional study of school-age children from Bogotá, Colombia. Methylation of LINE-1 repetitive elements was quantified in 568 children 5-12 years of age using pyrosequencing technology. We examined the association of LINE-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 47 publications
5
33
0
1
Order By: Relevance
“…For example, 7 out of 8 prior studies in this area found evidence of an association between at least one measure of life course SES and DNAm, [11][12][13][14][16][17][18] which is consistent with the results of this study. Similar to Borghol et al, 11 who found little overlap in DNAm patterns associated with childhood and adult SES, we found that childhood SES was associated with DNAm in AVP, FKBP5, OXTR, CCL1, CD1D, and F8, while adult SES was associated with DNAm in a somewhat different set of genes, including AVP, CD1D, F8, KLRG1, NLRP12, and TLR3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, 7 out of 8 prior studies in this area found evidence of an association between at least one measure of life course SES and DNAm, [11][12][13][14][16][17][18] which is consistent with the results of this study. Similar to Borghol et al, 11 who found little overlap in DNAm patterns associated with childhood and adult SES, we found that childhood SES was associated with DNAm in AVP, FKBP5, OXTR, CCL1, CD1D, and F8, while adult SES was associated with DNAm in a somewhat different set of genes, including AVP, CD1D, F8, KLRG1, NLRP12, and TLR3.…”
Section: Discussionsupporting
confidence: 90%
“…A handful of studies have investigated associations between SES and DNAm in infants and children. Perng et al 16 found that maternal education was positively associated with global DNAm in boys (but not girls) in a subset of 568 children from the Bogota School Children Cohort. Obermann-Borst et al 17 found that maternal education was associated with increased DNAm in a gene related to the insulin pathway in a sample of 120 children at 17 months of age; and Appleton et al 18 found that maternal education was associated with decreased placental DNAm in a gene related to the inactivation of maternal cortisol in a study of 444 healthy newborns.…”
Section: Introductionmentioning
confidence: 99%
“…Spearman’s correlation coefficients ranged from 0.06 to 0.56 for the LINE-1 sites and from 0.44 to 0.66 for the Alu sites. Because the distributions and correlations of %5mC differed by site for both repetitive elements, we used mixed effects linear regression models to derive a single estimate of LINE-1 and Alu for each individual according to previously described methods [10]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, methyl-donor micronutrient intake was not related to LINE-1 methylation among 149 healthy adults in Texas [8], while a study of 165 cancer-free adults in New York found a positive correlation with folate intake [9]. In Colombian schoolchildren, neither erythrocyte folate nor serum vitamin B12 were associated with LINE-1 methylation [10]. Two perinatal studies examined the relations of maternal nutrient intake with LINE-1 methylation during early life [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that human embryonic stem cells treated with retinoic acid change the pattern of global and specifi c methylation (Cheong et al 2010 ), suggesting that diet can infl uence gene expression profi les at germinal centers by altering the pattern of DNA methylation. A recent study in school-age children has reveal a differential correlation between the levels of methylation of a repetitive sequence in the DNA (LINE-1) and the circulating levels of vitamin A (retinol) and with C-reactive protein (Perng et al 2012 ), suggesting that methylation of this repeated DNA element may play a role in modifying infl ammatory responses and that vitamin intake may help modifying those responses.…”
Section: Effect Of Dietmentioning
confidence: 99%